Agroforestry for food security - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Emmanuel Mutamba of the Green Living Movement describes how agroforestry is improving food security and farm income in central Zambia.